Proposal of Two Measures of Complexity Based on Lempel-Ziv for Dynamic Systems: An Application for Manufacturing Systems. (29th January 2018) - Alfaro, Miguel; Vargas, Manuel; Fuertes, Guillermo; Sepúlveda-Rojas, Juan Pedro
Abstract : The measure of complexity of Lempel-Ziv (LZC) is used for the analysis of time series generated by dynamic systems with the objective of determining its complexity. This work measures LZC of different series coming from periodic functions, probabilistic functions, and chaotic systems. Later, these metrics of complexity are applied to the average of the number of parts in the waiting line in a manufacturing workshop. The results demonstrate the efficiency of the LZC to establish the level of the dynamic behavior of the manufacturing systems, through the time series.